Digital Technologies Application and Competitive Advantage for MSMEs Sustainability and Market Performance - Dekeng Setyo Budiarto; Ayuk Amanda; Norraini Nordin (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2023)
The development of digital technology and intense competition have forced owners of small firms (MSMEs) to adapt technological developments to compete with competitors quickly. This study examines the effect of digitalization and competitive advantage on market sustainability and performance. This study used a qualitative method by distributing questionnaires to 166 MSMEs owners in Indonesia. The finding of this research indicate that digitalization and competitive advantage affect sustainability and market performance. This study's results suggest to MSMEs owners that technological proficiency is crucial for companies to survive in an uncertain environment.